PROFESSIONAL SELF-CREATION AS A SUBJECT OF SCIENTIFIC PSYCHOLOGICAL RESEARCH (Psychology Travelogs, 2021)
The article presents a theoretical analysis of personal self-creation and professional self-creation. The concepts, structure, conditions, factors and results of self-creation of personality were considered based on a review of scientific literature sources. It was found that professional self-creation has not yet been the subject of a separate scientific study. Based on the obtained theoretical data, the definition of professional self-creation is formulated and assumptions are made about its components, conditions, factors and results. In particular, the article states that professional self-creation is an internally determined activity aimed at creating a person's professional "І", defining their own professional meanings and improving their professional efficiency. Among the components of professional self-creation, the authors of the article included: professional self-improvement and self-education; increase of own professional efficiency; embodiment in professional activity of the system of own value orientations; striving for professional autonomy; realization by the expert of the professional purposes, intentions, plans. According to the authors of the article, the conditions that activate professional self-creation are spirituality, ethics and humanistic values, which, in turn, determine all other conditions, such as: voluntariness, the presence of a personal desire to engage in professional self-creation; the ability of a specialist to plan activities for professional self-creation; adequate attitude to oneself and one's profession, adequate professional self-esteem. The internal and external factors of professional self-creation are distinguished: internal - own activity and independence of the specialist, based on own desire of professional development; external - stimulation from the family, enterprise, institution, organization where the person works. The proposed theoretical provisions require further empirical verification.
Keywords: self-creation of personality, professional self-creation; self-improvement; self-development; self-actualization; professional self-development; professional self-actualization; professional self-improvement